Bridging individual, group, class, and outside world in online courses - Dalsgaard, Christian; Caviglia, Francesco; Thestrup, Klaus (Proceedings of the International Conference on Networked Learning, 2026)
The paper explores how educational programmes can be designed to encompass and connect activities at multiple levels of student engagement — from individual work and group collaboration to class activities and interaction with external stakeholders. The study takes as its point of departure the framework of digital learning spaces, which distinguishes between four spaces for learning: the individual space, the working group, the community of interest, and open connections. Through an empirical case study, the paper investigates how student activities can bridge these learning spaces, and how students experience activities that move between them. The case study is based on the Master’s programme in IT-based Educational Design at Aarhus University, Denmark. Data were collected through a survey (n=46) including six open questions about students’ experiences with activities related to the different levels of learning spaces: group blogging, commenting on blog posts, social annotation, open feedback on assignments, collaboration between students, and dissemination to the outside world. The study examines how the programme succeeds in 1) strengthening of individual student agency of the student, 2) supporting collaborative group work, 3) mobilising and utilising the collective resources of a class, and 4) engaging students in interactions with society. The findings show that students are generally able to move between and participate meaningfully in all four learning spaces. Digital collaboration tools are perceived as highly supportive of close cooperation in distributed groups. Social annotation and open feedback practices are experienced as valuable mechanisms for connecting individual and class-level activities, although they may also challenge students’ sense of personal boundaries and study habits. Activities that extend learning beyond the institutional framework, such as public webinars and workshops, are described as particularly rewarding, creating a sense of professional identity and relevance. The study concludes that designing for digital learning involves not only supporting distinct learning spaces but also creating bridges that enable transitions between them. Attention to the tensions and boundary-crossing between spaces is essential for fostering coherence, inclusion, and meaningful engagement in digital learning spaces.